Countering Violent Extremism in Sub-Saharan Africa: What Policy Makers Need to Know. (September 2019) - Hardy, Robin A.
This essay addresses recurring and growing inaccurate reports from political officials as well as counter-terrorism analysts and journalists that the Sahara-Sahel group Boko Haram is a defeated entity. Notwithstanding concerted efforts to rout the movement, Boko Haram and its network of jihadists have expanded. Crucial misunderstandings surrounding what fostered and sustains the phenomenon—as well as a general naivety regarding the organization's flexibility to adapt to attract combatants, financial support, and weaponry beyond Nigeria's borders—have made performing basic adequate risk assessments overwhelmingly challenging. Policy makers and CVE (Countering Violent Extremism) practitioners would be wise to recognize that not only has Boko Haram morphed but its growing affiliates also terrorize increased territory. The threat of militant Islam in the Sahara-Sahel, therefore, has not been contained as some would have us believe. Rather, Muslim extremism has become entangled and more complex not only in Africa but across the Muslim world. When jihadists in one territory have taken a beating, surviving fighters have simply relocated to other geographies accompanied by connections for capital and munitions. In this way, Boko Haram—the fulcrum of violent Islam in the Sahara-Sahel—has become, over time, an international jihadist actor.